C-C Bond Activation of a Cyclopropyl Phosphine: Isolation and Reactivity of a Tetrameric Rhodacyclobutane - Chaplin, AB; Weller, A (2010)
Reaction of the functionalized phosphine P tBu 2CH 2(C 3H 5) with [Rh(C 8H 14) 2Cl] 2 (C 8H 14 = cis-cyclooctene) resulted in selective C-C bond activation of the cyclopropyl group and formation of a tetrameric rhodacyclobutane, [RhCl(- 3-P tBu 2CH 2CH(CH 2) 2)] 4, which was characterized in the solid state by X-ray crystallography. This complex acts as a latent source of the [Rh(- 3-P tBu 2CH 2CH(CH 2) 2)] + fragment, forming a range of new complexes by salt metathesis with NaCp, [RhCp(- 3-P tBu 2CH 2CH(CH 2) 2)], chloride abstraction in the presence of arenes, [Rh(- 6-arene)(- 3-P tBu 2CH 2CH(CH 2) 2)][BAr F4] [arene = C 6H 5F, C 6H 3Me 3; Ar F = 3,5-C 6H 3(CF 3) 2], or fragmentation by addition of phosphine ligands, trans-[RhCl(PR 3)(- 3-P tBu 2CH 2CH(CH 2) 2)] (R = iBu, Cy). In contrast, reaction with carbon monoxide results in the reductive elimination of the tethered cyclopropane, demonstrating reversible C-C bond activation, and formation of cis-[RhCl(CO) 2(P tBuCH 2(C 3H 5))]. These complexes were characterized in solution by NMR spectroscopy and in the solid state by X-ray diffraction. Chloride abstraction from [RhCl(P iBu 3)(- 3-P tBu 2CH 2CH(CH 2) 2)] resulted in the regioselective isomerization of the tethered cyclopropane to a terminal alkene, viz., the formally 14-electron complex [Rh(P iBu 3)(- 3-P tBu 2CH 2CH 2CH - CH 2)][BAr F4], notable for the presence of a strong agostic interaction with a phosphine iBu substituent, apparent both from the solid-state structure and in solution by 1H NMR spectroscopy. Addition of hydrogen to this complex resulted in hydrogenation of the alkene and formation of [Rh(H) 2(P iBu 3)(P tBu 2nBu)][BAr F4]. These steps overall correspond to selective C-C bond functionalization (hydrogenation) of the tethered cyclopropane and are of direct significance to a related catalytic process [J. Am. Chem. Soc. 2003, 125, 886] and, more generally, to the rhodium-mediated transformation of alkanes. © 2010 American Chemical Society.